Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Establishment of reference mandibular plane for anterior alveolar morphology evaluation using cone beam computed tomography - Rong-yang Wang; Min Han; Hong Liu; Chun-ling Wang; Hong-hong Xian; Lei Zhang; Shi-jie Zhang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2012)

Cloning arginine kinase gene and its RNAi in Bursaphelenchus xylophilus causing pine wilt disease - Xin-rong Wang; Xi Cheng; Ya-dong Li; Jin-ai Zhang; Zhi-fen Zhang; Han-rong Wu (European Journal of Plant Pathology, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

Changes in Small Intestinal Morphology and Digestive Enzyme Activity with Oral Administration of Copper-Loaded Chitosan Nanoparticles in Rats - Xin-Yan Han; Wen-Li Du; Qi-Chun Huang; Zi-Rong Xu; Yi-Zheng Wang (Biological Trace Element Research, 2012)